The Influence Of Dominant Leadership And Group Cohesiveness On Groupthink Phenomenon In The Decision-Making Process: A Systematic Literature Review - Edi Priyanto; Nur Wening (Eduvest - Journal of Universal Studies, 2024)
In collective decision-making, a phenomenon known as "groupthink" can happen when individuals of the group have a tendency to agree with the majority view, even when that view is not supported by reason. The primary objective of this study is to examine how group cohesiveness and leadership affect groupthink and how it affects the standard of decision-making. The outcomes of earlier studies are analyzed in this study using a methodical literature review approach. According to study findings, group cohesiveness and dominant leadership can raise the possibility of groupthink. Two factors contribute to this: (1) Dominant leaders frequently dictate how decisions are made, which limits group members' ability to participate and conduct discussions; and (2) Cohesive groups typically have a high degree of mutual trust, which makes it comfortable for members to voice differing ideas. The effectiveness of the decision-making process might be negatively impacted by groupthink.